Acetylation reduces the ability of CheY to undergo autophosphorylation. Issue 1 (13th August 2013) - Li, Ru; Chen, Peng; Gu, Jing; Deng, Jiao‐Yu
Abstract CheY, the response regulator of the chemotaxis system in Escherichia coli, can be regulated by two covalent modifications – phosphorylation and acetylation. Both covalent modifications are involved in chemotaxis, but the mechanism and role of the acetylation are still obscure. While acetylation was shown to repress the binding of CheY to its target proteins, the effect of acetylation on the ability of CheY to undergo autophosphorylate with AcP is not fully investigated. To obtain more information on the function of this acetylation, we successfully expressed and purified CheY protein with a 6 × His‐tag on the C‐terminus. Subsequently, acetylated CheY (AcCheY) was obtained with AcCoA as the acetyl donor, and the acetylation level of AcCheY was confirmed by Western blotting and then mass spectrometry. Using tryptophan fluorescence intensity measurements as a monitor of phosphorylation, we showed that acetylation reduces the ability of CheY to undergo autophosphorylation.